A Comprehensive Analysis of the Cellular and EBV‐Specific MicroRNAome in Primary CNS PTLD Identifies Different Patterns Among EBV‐Associated Tumors. Issue 11 (4th August 2014) - Fink, S. E. K.; Gandhi, M. K.; Nourse, J. P.; Keane, C.; Jones, K.; Crooks, P.; Jöhrens, K.; Korfel, A.; Schmidt, H.; Neumann, S.; Tiede, A.; Jäger, U.; et al.
<x xml:space="preserve">Abstract</x> Primary central nervous system (pCNS) posttransplant lymphoproliferative disorder (PTLD) is a complication of solid organ transplantation characterized by poor outcome. In contrast to systemic PTLD, Epstein–Barr virus (EBV)‐association of pCNS PTLD is almost universal, yet viral and cellular data are limited. To identify differences in the pattern of EBV‐association of pCNS and systemic PTLD, we analyzed the expression of latent and lytic EBV transcripts and the viral and cellular microRNAome in nine pCNS (eight EBV‐associated) and in 16 systemic PTLD samples (eight EBV‐associated). Notably although 15/16 EBV‐associated samples exhibited a viral type III latency pattern, lytic transcripts were also strongly expressed. Members of the ebv‐miR‐BHRF1 and ebv‐miR‐BART clusters were expressed in virtually all EBV‐associated PTLD samples. There were 28 cellular microRNAs differentially expressed between systemic and pCNS PTLD. pCNS PTLD expressed lower hsa‐miR‐199a‐5p/3p and hsa‐miR‐143/145 (implicated in nuclear factor kappa beta and c‐myc signaling) as compared to systemic PTLD. Unsupervised nonhierarchical clustering of the viral and cellular microRNAome distinguished non‐EBV‐associated from EBV‐associated samples and identified a separate group of EBV‐associated pCNS PTLD that displayed reduced levels of B cell lymphoma associated oncomiRs such as hsa‐miR‐155, ‐21, ‐221 and the hsa‐miR‐17‐92 cluster. EBV has a major impact on viral and cellular microRNA expression in EBV‐associated pCNS PTLD.